Computational Modeling of Membrane Viscosity of Red Blood Cells (Communications in Computational Physics, 2018)
Despite its demonstrated importance in the deformation and dynamics ofred blood cells, membrane viscosity has not received the same attention in computationalmodels as elasticity and bending stiffness. Recent experiments on red blood cellsindicated a power law response due to membrane viscosity. This is potentially muchdifferent from the solid viscoelastic models, such as Kelvin-Voigt and standard linearsolid (SLS), currently used in computation to describe this aspect of the membrane.Within the context of a framework based on lattice Boltzmann and immersed boundarymethods, we introduce SLS and power law models for membrane viscosity. Wecompare how the Kelvin-Voigt (as approximated by SLS) and power law models alterthe deformation and dynamics of a spherical capsule in shear flows.